THE PROFILE OF THE HOUSEHOLD POVERTY AT THE VILLAGE OF AUA KUNIANG PASAMAN DISTRICT OF WEST PASAMAN REGENCY - Yulianti, Nova; Erita, Yeni; U, Iswandi (STKIP PGRI Sumbar, 2013)
The trends of population growth at the village of Aua Kuniang fall to speed category; it can be seen in 2012 where this village has the population about 22.429 people. However by having a quickly population growth was not followed with enlarging of job opportunity and the farming land was still more restricted. Seeing from their income, there is unbalance with their essential needs. The lower income household, of course will be difficult to fulfill their essential needs for example food, dress, resident, health and education. For that reason, the unbalance triggers the occurrence of poverty at the village of Aua Kuniang Pasaman District of West Pasaman Regency. The type of this research was descriptive. The population of this research was all poor household leaders lived at the village of Aua Kuniang Pasaman District of West Pasaman Regency totally 1.731 of household leaders. Technique of taking sample used proportional random sampling by the proportion about 10% from all existing samples with total of them about 173 of household leaders. Technique of data collection was done by the observation or distribution the questionnaire to respondent. Technique of data analysis in this research used percentage analysis toward the profile of poor household. The result of research showed that 1) the condition of dress was not fulfilled well, the poor household have just two kinds of dress with total respondents 42,8%, 2) the condition of their food was not fulfilled well, because they have never consumed some fruits with total respondents about 61,3%. 3) the resident condition was lower, where the wall of their house made from woodÂ Â Â construction irregularly with total respondents 67,1% and small size (+ 4 x 6 meter) with total respondent about 41,1%. 4) The health condition was well enough, but the cost of medical need was still supported by Jamkesmas (society health guarantee) with total respondents about 90,2%. 5) The education condition, where almost part of respondents was under of elementary school up to elementary school level about 42,2%. And the household leader who have never the informal education about 100%.